Fan identification and national identity. Issue 3 (4th March 2019) - Erik Meier, Henk; Utesch, Till; Raue, Charlotte; Uhlenbrock, Christina; Chababi, Nabila; Strauss, Bernd
Abstract: It is commonly assumed that sport plays an important role for national identity. However, empirical research has primarily focused on sport's role for emotional-affectice rather than cognitive aspects of national identity. Therefore, research presented here explores whether identification with the German national soccer team serves to reinforce ethnic or civic conceptions of national identity. Analyses of a unique dataset conducted during the 2014 FIFA World Cup and the 2016 EURO show that national team identification is an important determinant of national pride and national belonging. Respondents who identify with the national soccer team can adhere to different conceptions of national identity. It seems that national pride and affection as well as conceptions of national identity represent stable attitudes not affected by the success of the national team. Further research should improve conceptual clarity and measurement.